If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -7 = 14.1 Reorder the terms: -7 + Y = 14.1 Solving -7 + Y = 14.1 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + Y = 14.1 + 7 Combine like terms: -7 + 7 = 0 0 + Y = 14.1 + 7 Y = 14.1 + 7 Combine like terms: 14.1 + 7 = 21.1 Y = 21.1 Simplifying Y = 21.1
| 240=x-60 | | 25-6[(2-7)-(-5-7)]= | | 6(2x-5)=5(3x+7) | | 7(4x+1)=5(4x+3) | | 3(5-4x)=3(3x+4) | | 5(X+3)+(2X-7)=3X-9 | | 1/3,47/6 | | 82-k=37 | | x^2-3x+62=0 | | 240=x+75 | | 5x-7=2x-67 | | X+4(4x+16)=21 | | 9(n+1)=3(n-5) | | 4x+50=130 | | (5w-8)(9-w)=0 | | y=x^2-2.4x-2.2 | | -5(-8x+5)+3x=-369 | | (W+2)(w-5)= | | 2y+10=3y | | 0=2w^2-3w-44 | | 8(-8+8k)=-192 | | 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k |